Síndrome de fragilidade em pacientes com insuficiência cardíaca ambulatoriais - Guterres, Jéssica Pippi (2024)
Considered an important public health problem, affecting almost 64 million people, heart failure (HF) is a clinical syndrome with symptoms and/or signs caused by a structural and/or functional cardiac abnormality and corroborated by elevated levels of natriuretic peptide and/or objective evidence of pulmonary or systemic congestion. When presented together with frailty syndrome (FS), it is associated with worse clinical outcomes, poor prognosis and increased complexity of care. In view of the above, and considering the systemic impairments of FS, there is a need for further elucidation about the development and manifestations in patients with HF. This study aims to evaluate and identify the association of the muscular architecture of the quadriceps femoris, respiratory muscle strength, peripheral muscle endurance and FS in patients with HF under outpatient treatment. This is a cross-sectional study. Individuals with HF, of both genders, over 18 years of age, followed at the Cardiology Outpatient Clinic of the University Hospital of Santa Maria, were evaluated and underwent the following assessments: assessment of FS through the Physical Phenotype, muscular architecture of the quadriceps femoris, respiratory muscle strength and peripheral muscle resistance. Forty individuals were included, the majority of whom were female (52.5%), with a mean age of 61.5 ± 8.28 years and a mean left ventricular ejection fraction of 46.5 ± 12.09%. The prevalence of the pre-frailty phenotype was 55% and the frailty phenotype was 45%. Maximum expiratory pressure, echogenicity, peripheral muscle resistance and the dominant lower limb were associated with FS. Given this, this study allowed a better understanding of the multifactorial aspects involved in physical frailty in patients with HF under outpatient treatment.